Longitudinal course of behavioural and psychological symptoms of dementia: a systematic review - van der Linde, Rianne M.; Dening, Tom; Stephan, Blossom C.M.; Prina, A. Matthew; Evans, Elizabeth; Brayne, Carol (Royal College of Psychiatrists, 2016)
Background More information about the pattern of Behavioural and Psychological Symptoms of Dementia (BPSD) in the course of dementia is needed to inform patients and clinicians and to design future interventions.